Optimizing the aerobic performance of junior football players through small-sided football games training - Sîrbu Marius; Hanțiu Iacob (Editura Universităţii din Oradea, 2021)
Training with small-sided games proved to be effective in the training of football players. The purpose of this study was to analyze whether participation in a training programme with small-sided football games resulted in the development of the aerobic capacity. The subjects of this study were 40 16-18-year-old athletes divided into two equal groups: experiment group (GE) and control group (GC). Both groups participated in training programmes from 6.07.2020 to 27.11.2020 - GE in a small-sided football training programme; GC in a classic exercise training programme. The following equipment was used: Hosand GTa - to measure HR - and the WittyGateMicrogate2 system for timing of the samples taken. Subjects took the YIRTL1 sample. The data collected was processed with the SPSS programme, variant 23. In the YIRTL field trial there were no significant differences in the initial testing (IT) between the two groups, but in the final testing (FT) the differences were significant. Thus, at FT the difference between the score means of the two groups was significant both for the covered distance parametre (U = 4,00, N1 = 20, N2 = 20, two-tailed p =,000, d = 3,35) and for the parametre indicating the hold time in the aerobic zones <81%FCmax (U = 82,50, N1 = 20, N2 = 20, two-tailed p =,001, d = 1,21). The study revealed that the aerobic capacity developed by implementing a small-sided football games training programme for 21 weeks.